PENGEMBANGAN E-LKPD BERBASIS MODEL GAME BASED LEARNING BERBANTUAN BLOOKET PADA PEMBELAJARAN PAI-BP TERHADAP MINAT DAN HASIL BELAJAR PESERTA DIDIK KELAS X SMA - Zilfadlia Nirmala; Milya Sari; Muhammad Zalnur (STKIP Pesisir Selatan, 2026)
Objective: This research aims to develop a student e-worksheet (e-LKPD) based on a game based learning model assisted by blooket on the learning of Islamic Religious Education and Ethics of insurance, banks, and sharia cooperatives in high school class X. This research is motivated by the still dominance of the use of conventional teaching materials that have not fully supported students' interests and learning outcomes, especially in conceptual and abstract materials. This research is a research and development by adapting the Plomp development model which includes three stages, namely preliminary research, prototyping phase, and assessment phase. The research data was collected through observation of learning implementation, validation and practicality questionnaires, learning interest questionnaires, and student learning outcome tests, then analyzed descriptively, quantitatively, and qualitatively. The results of the study show that the e-LKPD based on game based learning assisted by blooket that was developed met very valid criteria based on expert assessment, practical in the implementation of learning, and effectively used in supporting students' interests and learning outcomes. The novelty of this research lies in the development of digital e-LKPD that integrates the game based learning model with the blooket platform systematically through the Plomp model in PAI and Ethics learning, so that it can be an alternative to innovative teaching materials that are relevant to the characteristics of 21st century learning.